1995
DOI: 10.1111/j.1365-2249.1995.tb08356.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor-alpha (TNF-α) in the host resistance to mycobacteria of distinct virulence

Abstract: SUMMARYThe relative virulence of different isolates of Mycobacterium avium has been linked to their capacity to trigger the secretion of TNF from the macrophages they infect. H37Ra, which is very active in inducing TNF release due to its lipoarabinomannan moiety, was used to compare with the previous results. The growth ofH37Ra in macrophages was increased in vitro by the neutralization of TNF and neutralization of either TNF and/or interferon-gamma (IFN-I') enhanced the in vivo proliferation of this microbe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
1
31
0
Order By: Relevance
“…Although morphotypes of the same strain are very closely related, previous studies have demonstrated that the smooth-transparent variant is usually better able to survive and grow intracellularly than the opaque morphotype (21,22). With regard to the M. avium morphotypes used in this study (2151 SmT and SmO), this pattern has been confirmed both in murine macrophages and in a mouse model of infection (23,24).…”
supporting
confidence: 67%
“…Although morphotypes of the same strain are very closely related, previous studies have demonstrated that the smooth-transparent variant is usually better able to survive and grow intracellularly than the opaque morphotype (21,22). With regard to the M. avium morphotypes used in this study (2151 SmT and SmO), this pattern has been confirmed both in murine macrophages and in a mouse model of infection (23,24).…”
supporting
confidence: 67%
“…Moreover, we observed significantly higher levels of TNF-␣ secreted by M tuberculosis H37Ra-infected BMMs compared with H37Rv-infected BMMs, as observed previously. 37 The TNF-␣ produced by H37Ra-but not H37Rv-infected BMMs was also significantly decreased in cells treated with the 2A11 blocking antibody compared with untreated or isotype control ( Figure 6B). …”
Section: Dectin-1 Facilitates Tnf-␣ Production In Macrophages Infectementioning
confidence: 89%
“…Unlike M. tuberculosis, however, M. avium proliferation in vivo in mice is under the control of the Nramp1 gene (Appelberg & Sarmento, 1990 ;Medina et al, 1996). NRAMP1 is a transmembrane protein expressed in endosomal and phagosomal membranes of macrophages, that contributes to inhibition of growth of several intracellular pathogens, including Mycobacterium bovis, M. avium, Leishmania donovani and Salmonella typhimurium (Gruenheid & Gros, 2000).…”
Section: Discussionmentioning
confidence: 99%